The Mangrove Communities of Danjugan Island, Cauayan, Negros Occidental, Philippines - King, Richard; Turner, Craig; Dacles, Terence; Solandt, Jean-Luc; Raines, Peter (Silliman Journal, 2022)
The mangroves of the Philippines have declined by 75% over the past 80 years due to a range of anthropogenic pressures. However, there is relatively little information available on mangrove stands in the central Visayas region of the Philippines. This paper represents the first detailed inventor), of the mangrove resources of Danjugan Island, Cauayan, Negros Occidental, an island with relatively undisturbed mangal communities. The results of the completed inventory of all mangroves of the island suggest that the island supports very diverse (14 true mangrove species identified) and abundant communities that vary with location on the island. These are discussed in terms of the geographic location and potential conservation value.